Awareness of physicians and pharmacists of aldosterone antagonists in heart failure and myocardial infarction in Jordan - Mayyas F; Ibrahim K; Alzoubi KH (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Objective: to evaluate physicians and clinical pharmacists' awareness and practices regarding use of aldosterone antagonists in heart failure (HF) and post-myocardial infarction (MI). Methods: First, we reviewed the prescription of aldosterone antagonists among 408 patients presenting to the cardiology clinic at a major hospital in Jordan. Second, physicians and pharmacists working in cardiovascular departments completed a questionnaire related to use of aldosterone antagonists in HF and post-MI. Results: Thirty patients (7.59%) were eligible for aldosterone antagonist; only 4 received them at discharge (13.3%). The survey was completed by 153 professionals (response rate 76.12%). About 72.1% of participants were aware of studies regarding use of aldosterone antagonists post-MI and in HF. Moreover, 10.45%/53.6% of participants strongly agreed/agreed that these agents are useful in normotensive post-MI and HF patients. Spironolactone was the most prescribed drug by 92.1% of participants. About 41.8% of participants reported use of spironolactone in post-MI and HF. With respect to guidelines, only 39.2% of participants agreed that adding spironolactone to standard therapy in HF is recommended, and 48.3% agreed on adding it directly post-MI. Clinical pharmacists and cardiologists were generally more aware of guidelines than pharmacists, cardiac surgeons and residents/fellows. Conclusions: there is an under-use of aldosterone antagonists in HF and post-MI patients, and a lack of detailed awareness of current guidelines among health care providers. Dissemination of evidence-based guidelines and usage protocols may improve management of post-MI and HF.